Development And Quality Evaluation Of Low-Fat Chicken Nuggets Incorporated With Brown Rice Flour - kumar, K Ajay; Gupta, R S Dilip; Devathkal, S K; Rao, B Eswara; subhasini, N (Journal of Meat Science, 2024)
Chicken nuggets prepared by incorporating three different levels of brown rice flour along with other non-meat ingredients. The formulations prepared were – Control (0% brown rice flour), T1(2% brown rice flour), T2(4% Brown rice flour), T3(6% Brown rice flour). Among different treatments, brown rice flour at 6% produced significantly (P
Keywords: Brown rice flour; chicken nuggets; water holding capacity; texture profile analysis and proximate analysis